Prestressed concrete beam and preparation method thereof
By using concrete slurry of nanosilicon dioxide, natural zeolite and other materials and post-tensioning prestressing technology, the problems of concrete beam deformation and cracking, slow early strength growth and high cost are solved, and higher compressive strength and tensile strength are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411498803.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Existing concrete beams are prone to deformation and cracking after long-term use, and the early strength increases slowly and the cost is high.
The concrete slurry composed of nano silica, natural zeolite, fly ash and ordinary cement is used to optimize the composition and production process of concrete through post-tensioning method prestressing and high-temperature curing.
Significantly reduces shrinkage and creep of concrete beams, improves compressive and tensile strength, reduces costs, and accelerates curing speed and early strength growth.
Smart Images

Figure CN119551946A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a prestressed concrete beam and a preparation method thereof. Background Art
[0002] Concrete beams are a widely used building material that combines the compressive strength of concrete and the tensile strength of steel bars, and have excellent compressive resistance and durability. However, concrete beams in the prior art also have some inherent defects, such as shrinkage and creep. Shrinkage refers to the natural reduction in volume of concrete during the hardening process. Shrinkage can cause tensile stress inside the concrete, which in turn causes cracks; creep refers to the inelastic deformation of concrete under continuous load, that is, the phenomenon that concrete continues to deform under constant load over time. Shrinkage and creep can cause deformation, cracks and prestress loss in concrete structures, affecting the safety and durability of the structure. The prior art method for dealing with shrinkage and creep of concrete beams adopts anti-shrinkage and creep design solutions or uses materials of higher standards.
[0003] The existing methods for treating shrinkage and creep of concrete beams have the following problems:
[0004] (1) Adopting a structural solution that resists shrinkage and creep, such as reserving a margin in the structural dimensions during the design and construction of concrete beams to compensate for shrinkage deformation. However, this method does not substantially solve the problem and quality problems will still occur due to shrinkage and creep.
[0005] (2) Use materials of higher standards, such as large amounts of high-performance cement, mineral admixtures, or other materials that can only be used after complex processing. However, the use of large amounts of high-standard materials will also bring high concrete costs. In addition, the early strength growth of concrete beams using materials such as high-performance cement and mineral admixtures is slow, the curing time is long, and a complex and stable material supply chain is often required, which has a significant impact on construction progress and costs. Summary of the invention
[0006] 1. Technical issues to be resolved
[0007] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a prestressed concrete beam and a preparation method thereof, which solves the problems existing in the prior art that the concrete beams suffer from more deformation and cracking after long-term use, the early strength growth of the concrete beams is slow, and the cost is too high.
[0008] (II) Technical solution
[0009] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0010] In a first aspect, the present invention provides a method for preparing a prestressed concrete beam, comprising the following steps:
[0011] S1: Mixing cement, fly ash, fine aggregate and coarse aggregate to obtain dry material;
[0012] S2: mixing nano-silicon dioxide, natural zeolite and water, and performing ultrasonic dispersion to obtain a dispersion; mixing and stirring the dry material and the dispersion to obtain a wet material;
[0013] S3: adding a water reducing agent to the wet material and stirring to obtain a concrete slurry;
[0014] S4: pouring concrete slurry into a post-tensioned prestressed concrete beam mold, and then performing a first curing to obtain a concrete beam blank, the curing temperature being 35-55° C.; applying prestress to the concrete beam blank to obtain a prestressed concrete beam blank;
[0015] S5: performing a second curing on the prestressed concrete beam blank at a curing temperature of 40-65° C., and obtaining a prestressed concrete beam after curing;
[0016] In parts by weight, cement is 400-600 parts, fly ash is 10-50 parts, fine aggregate is 400-1000 parts, coarse aggregate is 800-1200 parts, natural zeolite is 5-25 parts, nano silicon dioxide is 1-10 parts, water is 100-200 parts, and water reducing agent is 1-10 parts; the glue-water ratio of the concrete slurry is 1:0.28-0.4.
[0017] According to a preferred embodiment of the present invention, in step S1, the fine aggregate is at least one of natural sand and machine-made sand; the coarse aggregate is at least one of coarse aggregates made of mine crushed stone, slag, granite, basalt and construction waste; the mass of fine aggregate with a particle size in the range of 0.315 mm to 2.36 mm in the fine aggregate should account for 30-50% of the total mass of the fine aggregate, and the mass of coarse aggregate with a particle size in the range of 4.75 mm to 19.5 mm in the coarse aggregate should account for 30-50% of the total mass of the coarse aggregate.
[0018] According to a preferred embodiment of the present invention, in step S1, the cement is silicate cement, and the particle size of the cement is 10-25 μm; the particle size of the fly ash does not exceed 20 μm, and the SiO2 content in the fly ash is 15-55wt%, and the Al2O3 content is 5-30wt%.
[0019] According to a preferred embodiment of the present invention, in step S2, the particle size of nano-silicon dioxide is 1-100 nm, and the purity is ≥95%; the mass of nano-silicon dioxide with a particle size not exceeding 40 nm should account for 30-50% of the total mass of the coarse aggregate.
[0020] According to a preferred embodiment of the present invention, in step S2, the natural zeolite is at least one of analcime, lazurite, phillipsite, natrolite, mordenite, heulandite, clinoptilolite, chabazite and faujasite; the particle size of the natural zeolite is 10 μm-1 mm, and the porosity is 20-50%.
[0021] According to a preferred embodiment of the present invention, in step S2, the ultrasonic frequency of ultrasonic dispersion is 60kHz-90kHz, and the dispersion time is 10-100min.
[0022] According to a preferred embodiment of the present invention, in step S3, the water reducing agent is at least one of naphthalene-based, melamine-based, aminosulfonate-based and aliphatic-based.
[0023] According to a preferred embodiment of the present invention, in step S4, layered pouring is adopted during pouring; during the pouring process, the concrete is vibrated and dispersed while pouring; during the first curing, the curing time is 3-7 days, and the air humidity is 90-100%; in step S4, after curing for A days, the temperature condition of the first curing is determined according to the following formula:
[0024] f c(T) =f0(1+α·(T-T0))·e ^(-β·(Ttop-T))
[0025] T0: reference curing temperature, selected according to the standard curing temperature of ordinary concrete;
[0026] f0: reference curing strength, i.e., the strength of concrete after curing for A days at the reference curing temperature T0, in MPa;
[0027] T: actual curing temperature;
[0028] f c(T) : Actual strength, i.e. the concrete strength after curing for A days at the actual curing temperature T, in MPa;
[0029] T top : Hydration active temperature, the temperature at which concrete hydration reaction is most active, measured by experiment;
[0030] α: early strength growth coefficient, 0<α≤0.1, unitless;
[0031] β: active variation coefficient, 0<β≤0.1, unitless;
[0032] T0, T, and T top Only the value is taken, no unit is taken; 3≤A≤7.
[0033] According to a preferred embodiment of the present invention, in step S5, during the second curing, the curing time is 1-10 days and the air humidity is 90-100%.
[0034] In a second aspect, the present invention provides a prestressed concrete beam prepared by the preparation method provided in the first aspect.
[0035] (III) Beneficial effects
[0036] The present invention discloses a prestressed concrete beam, which is obtained by curing concrete slurry. The concrete slurry contains raw materials such as nano-silicon dioxide, natural zeolite, fly ash, ordinary cement, fine aggregate, coarse aggregate, etc., so that the cured concrete has a lower shrinkage and creep degree. The prestressed concrete beam is obtained by applying prestress in combination with the post-tensioning method. Compared with the prior art, the prestressed concrete beam has a greatly increased shrinkage resistance and creep resistance of the concrete beam after forming through the optimized design of the concrete slurry components, and the bearing capacity of the concrete beam is increased by applying prestress, and the influence of external load on the stress structure of the concrete beam is reduced, so as to reduce the long-term load of the concrete beam. The technical effect of preventing deformation and cracking after long-term use; the combination of nano-silica + natural zeolite + fine aggregate + coarse aggregate + ordinary cement also makes the concrete have good shrinkage resistance and creep resistance, while having the advantages of low cost, fast curing speed, rapid early strength growth of concrete beams and strong corrosion resistance. In addition, since the present invention does not involve high-performance or high-grade cement, modified materials or other materials that require complex physical and chemical treatment, there is no need to establish a complex supply chain, which further reduces the raw material cost and construction cost of the concrete beam of the present invention, and achieves the technical effect of accelerating the curing time of the concrete beam and reducing the cost of concrete raw materials.
[0037] Secondly, since the concrete in the concrete beam of the present invention adopts a combination of nano-silica + natural zeolite + ordinary cement, through the filling effect, gelling effect (volcanic ash reaction) and interface effect between nano-silica, natural zeolite and ordinary cement, the obtained concrete also has good compressive strength, tensile strength, density, corrosion resistance, durability and self-healing properties. It can also be stably fixed for a long time after applying strong prestress, which can reduce the loss of prestress and prevent prestress failure.
[0038] In addition, since a higher curing temperature is used in the curing stage during the preparation of the concrete beam of the present invention, the higher curing temperature intensifies the reaction between cement and other materials in the concrete, increases the hydration rate of cement, and causes the concrete beam to produce early pre-creep. Compared with the prior art, the early pre-creep of the concrete beam can greatly reduce the curing time of the concrete beam during the preparation process, so that the concrete beam can reach the predetermined strength earlier, shorten the construction time, and speed up the construction progress; at the same time, the early pre-creep of the concrete beam can also further reduce the shrinkage creep of the prestressed concrete beam in the later stage, and improve the overall performance of the concrete beam. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The elastic modulus test data diagram of Examples 1-2 and Comparative Examples 1-4;
[0040] Figure 2 The compressive strength test data of Examples 1-2 and Comparative Examples 1-4 are shown;
[0041] Figure 3 It is a graph of strain test data of Examples 1-2 and Comparative Examples 3-4. DETAILED DESCRIPTION
[0042] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0043] The present invention provides a method for preparing a prestressed concrete beam, comprising the following steps:
[0044] S1: Mix cement, fine aggregate and coarse aggregate to obtain dry material.
[0045] S2: Mix nano silicon dioxide, natural zeolite and water, and then disperse them by ultrasonication to obtain a dispersion; mix and stir the dry material with the dispersion to obtain a wet material.
[0046] S3: Add water reducing agent to the wet material and stir to obtain concrete.
[0047] S4: pouring concrete into the post-tensioned prestressed concrete beam mold, and after pouring, performing the first curing to obtain a concrete beam blank, and the curing temperature can be 35-55°C. Inserting prestressed tendons into the reserved channel tube in the concrete beam blank (reinforcement treatment), and then tensioning the prestressed tendons to the design stress level, and then using anchors to fix the prestressed tendons (tensioning treatment), after the fixing is completed, filling the reserved channel tube with a pipeline grouting agent and sealing it to obtain a prestressed concrete beam blank.
[0048] S5: performing a second curing on the prestressed concrete beam blank, the curing temperature may be 40-65° C., and a prestressed concrete beam is obtained after curing.
[0049] In parts by weight, cement can be 400-600 parts, fly ash can be 10-50 parts, fine aggregate can be 400-1000 parts, coarse aggregate can be 800-1200 parts, natural zeolite can be 5-25 parts, nano silicon dioxide can be 1-10 parts, water can be 100-200 parts, and water reducer can be 1-10 parts; the ratio of the total weight of the cementitious materials cement, fly ash, natural zeolite and nano silicon dioxide to the weight of water can be 1:0.28-0.4.
[0050] Preferably, in parts by weight, the cement may be 450-550 parts, the fly ash may be 20-40 parts, the fine aggregate may be 500-700 parts, the coarse aggregate may be 1000-1200 parts, the natural zeolite may be 10-20 parts, the nano-silicon dioxide may be 5-10 parts, the water may be 150-200 parts, and the water reducing agent may be 2-8 parts; the cement-water ratio, that is, the ratio of the total weight of the cementitious materials cement, fly ash, natural zeolite and nano-silicon dioxide to the weight of water may be 1:0.32-0.36.
[0051] Preferably, in step S1, the stirring time may be 60-300 s, and the stirring speed may be 60-120 r / min.
[0052] Preferably, in step S1, the fine aggregate may include at least one of natural sand and machine-made sand; the coarse aggregate may include at least one of mine crushed stone, slag, granite, basalt and coarse aggregate made of construction waste.
[0053] More preferably, the fine aggregate may include natural sand and machine-made sand; the coarse aggregate may include at least two of coarse aggregates made from mine crushed stone, slag, granite, basalt and construction waste.
[0054] Preferably, the mass of coarse aggregate within the range of 4.75 mm to 19.5 mm in the coarse aggregate should account for 30-50% of the total mass of the coarse aggregate, and the mass of fine aggregate within the range of 0.315 mm to 2.36 mm in the fine aggregate should account for 30-50% of the total mass of the fine aggregate.
[0055] Among them, the use of a large amount of coarse aggregate further reduces the cost of concrete raw materials without affecting the overall performance.
[0056] Preferably, in step S1, the cement is ordinary Portland cement with a grade of 52.5R, and the particle size of the cement may be 10-25 μm.
[0057] Preferably, in step S1, the particle size of the fly ash does not exceed 20 μm, the SiO2 content in the fly ash may be 15-55wt%, and the Al2O3 content may be 5-30wt%.
[0058] More preferably, in step S1, the SiO2 content in the coal ash may be 30-55wt%, and the Al2O3 content may be 20-30wt%.
[0059] Among them, the addition of fly ash can enrich the particle size gradient of silica. Through the coordinated effect of silica and alumina with nano-silica and natural zeolite, the strength, wear resistance, durability of concrete beams and the fluidity of concrete can be further improved.
[0060] Preferably, in step S2, the particle size of the nano-silicon dioxide can be 1-100 nm, and the purity is ≥95%; the content of the nano-silicon dioxide with a particle size not exceeding 40 nm in the nano-silicon dioxide is ≥50wt%.
[0061] Among them, the role of nano-silicon dioxide is:
[0062] (1) Fill the tiny pores inside the concrete, increase the density of the concrete, reduce the shrinkage caused by water evaporation, and improve the strength and stiffness of the concrete.
[0063] (2) React with cement hydration products (Ca(OH)2) (volcanic ash reaction) to generate more calcium silicate hydrate (CSH) gel, which enhances the compressive and tensile strength of concrete, accelerates the strength growth of concrete, and shortens the curing time of concrete.
[0064] (3) Improve the interfacial transition zone (ITZ) between aggregate and cement paste. Nanosilica can fill into the ITZ and promote hydration reaction, thereby increasing the bonding strength of the interface and reducing cracks in the interface area.
[0065] Preferably, in step S2, the particle size of the nano-silicon dioxide can be 1-40 nm.
[0066] Preferably, in step S2, the natural zeolite may include at least one of analcime, lazurite, phillipsite, natrolite, mordenite, heulandite, clinoptilolite, chabazite and faujasite; the particle size of the natural zeolite may be 10 μm-1 mm, and the porosity of the natural zeolite may be ≥20%.
[0067] More preferably, in step S2, the particle size of the natural zeolite may be 0.1 mm-1 mm, and the particle size of the natural zeolite is larger than the particle size of the cement.
[0068] Preferably, in step S2, the porosity of the natural zeolite may be 20-50%.
[0069] Among them, the role of natural zeolite is:
[0070] (1) Cement and other cementitious materials can react fully. Higher curing temperatures will lead to rapid loss of water in concrete, which may result in the inability of cement clinker and other cementitious materials to fully react with each other. The high water absorption capacity of natural zeolite can be used to release water after the rapid loss of water, promote the secondary hydration of unhydrated cement clinker and other cementitious materials, and improve the performance of prestressed concrete beams. At the same time, natural zeolite also has a certain volcanic ash reaction, which can react with Ca(OH)2 in cement hydration products to generate more CSH gel, further improving the high strength and durability of concrete beams.
[0071] (2) Improve the durability of concrete. Natural zeolite has excellent adsorption capacity and can adsorb harmful substances such as chloride ions and sulfate ions in concrete, thereby improving its corrosion resistance.
[0072] (3) Accelerate cement hydration. Natural zeolite uses its porous structure and the nano-silicon dioxide and water adsorbed in its pores to promote the cement paste near the natural zeolite to quickly produce calcium silicate hydrate (CSH) gel with the natural zeolite as the center. The CSH gels produced near different natural zeolites are interconnected to further improve the early strength of the concrete beam, making the concrete beam cure faster.
[0073] Preferably, in step S2, the ultrasonic frequency of ultrasonic dispersion can be 60kHz-90kHz, and the dispersion time can be 10-100min; the stirring time of mixing the dry material and the dispersion liquid can be 60-120s, and the stirring speed can be 40-80r / min. Ultrasonic dispersion is used to evenly disperse nano-silicon dioxide into the pores of water and natural zeolite, so that nano-silicon dioxide and natural zeolite can be better mixed with other materials; ultrasonic dispersion can also discharge the air that may remain in the pores of natural zeolite, so that natural zeolite can absorb more water. The air remaining in the pores of natural zeolite may cause more bubbles to form in the concrete beam, which needs to be removed.
[0074] Preferably, in step S3, the stirring time may be 60-120 s, and the stirring speed may be 100-150 / min.
[0075] Preferably, in step S3, the water reducing agent may include at least one of naphthalene-based, melamine-based, aminosulfonate-based and aliphatic-based.
[0076] Preferably, in step S4, layered pouring is adopted during pouring; during pouring, the concrete is vibrated and dispersed.
[0077] More preferably, in step S4, during pouring, the concrete is vibrated and dispersed by vibrating and dispersing, the vibration time can be 10-30s, the vibration frequency can be 4000-12000vpm, and the vibration point spacing can be 25-50cm. Vibrating can remove air bubbles in the concrete, promote the close arrangement of aggregates, thereby improving the density and strength of the concrete, and at the same time enable the nano-silicon dioxide to be better dispersed into the tiny pores and capillaries in the concrete.
[0078] More preferably, in step S4, during pouring, concrete is oscillated and dispersed by ultrasonic oscillation dispersion, and the ultrasonic frequency can be 20kHz-50kHz, and the dispersion time can be 5s-40s, and the dispersion point spacing of ultrasonic oscillation dispersion can be 50-200cm. Through ultrasonic oscillation dispersion, ultrasonic cavitation effect is utilized to disperse and fuse more evenly between materials in concrete, reduce the pores and bubbles in concrete, especially, so that nano silicon dioxide can be dispersed more evenly, and can be effectively filled into the tiny pores and capillaries in concrete; Ultrasonic oscillation dispersion can also make more nano silicon dioxide intervene in the ITZ between aggregate and cement paste, improve the microstructure of the interface transition zone, and improve the interface bonding strength, thereby reducing the micro cracks in the interface area, and reducing the overall shrinkage and creep of concrete. However, it is necessary to pay attention to the dispersion time and dispersion point spacing of ultrasonic oscillation dispersion to prevent aggregate precipitation, and ultrasonic oscillation dispersion needs to use an ultrasonic oscillator, which will increase a certain construction cost.
[0079] Preferably, in step S4, during the first curing, the curing temperature may be 35-55° C., the curing time may be 3-7 days, and the curing air humidity may be 90-100%. The concrete beam blank is cured to 75-90% of the design strength, and then the prestressed tendons are inserted (reinforcing tendon treatment).
[0080] More preferably, in step S4, during the first curing, the curing temperature may be 40-50°C.
[0081] More preferably, in step S4, during the first curing, the curing temperature may be 45°C.
[0082] Preferably, in step S4, after curing for A days, the temperature condition for the first curing is determined according to the following formula:
[0083] f c(T) =f0(1+α·(T-T0))·e ^(-β·(Ttop-T))
[0084] T0: reference curing temperature, selected according to the standard curing temperature of concrete, T0 in the present invention is generally 20°C;
[0085] f0: reference curing strength, i.e., the strength of concrete after curing for A days at the reference curing temperature T0, in MPa;
[0086] T: actual curing temperature, the curing temperature during the first curing;
[0087] f c(T) : Actual strength, i.e. the concrete strength after curing for A days at the actual curing temperature T, in MPa;
[0088] Ttop : Hydration active temperature, the temperature at which the concrete hydration reaction is most active, measured by experiment; in the present invention, the hydration active temperature is 43-47°C, preferably 45°C;
[0089] α: early strength growth coefficient, 0<α≤0.1, unitless;
[0090] β: active variation coefficient, 0<β≤0.1, unitless;
[0091] T0, T, and T top Only the value is taken, no unit is taken; 3≤A≤7.
[0092] This formula is only applicable to concrete beams prepared by the preparation method of the present invention, with fixed concrete formula and fixed preparation method. It is used to estimate the actual theoretical strength of concrete beams at different curing temperatures at a specific curing time, and can also be used to determine the theoretical curing temperature using the target strength. In reality, there are many interfering factors (such as the non-uniform porosity of natural zeolite), and the strength of concrete beams will not completely conform to the theoretical value. After the reinforcement treatment is performed, the equation does not hold due to the influence of the prestressed tendons.
[0093] Among them, a concrete beam specimen (or concrete block specimen) is prepared by the preparation method of the present invention. During the first curing, the concrete beam specimen is cured at a reference curing temperature (the standard curing temperature of concrete is used as a reference, and the standard curing temperature of concrete is generally 20±2°C, preferably 20°C); its strength when the curing time is A days is recorded, that is, the reference curing strength. Then, the strength development of two groups of concrete beam specimens prepared by the preparation method of the present invention at different actual curing temperatures is tested, and the strength of the two groups of concrete beam specimens when the curing time is A days, that is, the actual strength, is recorded. α and β are calculated; α is the early strength growth coefficient, 0<α≤0.1, and has no unit; the value of α will change according to the specific proportion of concrete (mainly affected by the changes in natural zeolite and nano-silica) and the properties of cement; the larger the α, the faster the concrete beam hardens. β is the active variation coefficient, 0<β≤0.1, unitless; the value of β will change according to the change in the activity of the concrete hydration reaction. The larger the β, the greater the impact of the temperature change on the concrete beam; all the above concrete beam specimens use the same concrete formula. After obtaining α and β, the formula can be used to estimate the strength of the concrete beam blank at different curing temperatures and a curing time of A days, facilitating the reinforcing bar treatment and other processes, provided that the concrete formula remains unchanged.
[0094] Preferably, in step S4, the prestressed tendons may be steel strands, steel wire bundles or heat-treated steel bars; the reserved hole pipes may be corrugated pipes, steel pipes or plastic pipes; the anchors may be clip-type anchors, support anchors, cone plug anchors, grip-type anchors or combined anchors; the pipe grouting agent may be one of a micro-expansion grouting agent, a non-shrinkage grouting agent, a high-performance cement-based grouting agent, an early-strength grouting agent, an ordinary Portland cement grouting agent, a corrosion-resistant grouting agent, a low-temperature grouting agent and a high-fluidity grouting agent.
[0095] Preferably, in step S4, different post-tensioning prestressed concrete beam molds are selected according to the design scheme of the concrete beam.
[0096] Preferably, in step S4, different prestressed tendons, anchors, reserved channel pipes and pipeline grouting agents are selected according to the design scheme of the concrete beam. Different prestressing magnitudes and prestressed tendon tensioning equipment are selected according to the design scheme of the concrete beam.
[0097] Preferably, in step S5, during the second curing, the curing temperature may be 40-65° C., the curing time may be 1-10 days, and the air humidity may be 90-100%, and the curing may be performed to the designed level.
[0098] Preferably, in step S5, during the second curing, the curing period is 1-10 days, the curing temperature may be 40-55° C., and the air humidity may be 90-100%.
[0099] More preferably, after the second curing, curing is continued for 0-90 days as required, the curing temperature may be 15-30° C., the air humidity may be 90-100%, and the curing is performed to the designed level. Different curing times and curing plans may be selected as required.
[0100] When the concrete beam is hydrated, a higher ambient temperature is provided to accelerate the hydration of the cement clinker and volcanic ash materials in the concrete, achieve early pre-creep, and reduce the shrinkage creep of the prestressed concrete beam in the later period.
[0101] The present invention also provides a prestressed concrete beam prepared by the prestressed concrete beam preparation method of the present invention, comprising concrete, prestressed tendons, common steel bars, a pre-hole pipe, a pipe grouting agent and an anchor.
[0102] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0103] Example 1
[0104] The present embodiment provides a prestressed concrete beam, including concrete, steel strands, ordinary steel bars, corrugated pipes, ordinary silicate cement grouting agents and clip-type anchors. The raw materials of the concrete are, by weight, 485 parts of cement, 31 parts of fly ash, 15.5 parts of clinoptilolite, 7.41 parts of nano-silicon dioxide, 301 parts of machine-made sand, 301 parts of natural sand, 802.9 parts of mine gravel, 344.1 parts of granite, 5.93 parts of aminosulfonate water reducer, and 189 parts of water; the water-cement ratio is 0.35; the chemical compositions of cement, fly ash, clinoptilolite and nano-silicon dioxide are shown in Table 1.
[0105] This embodiment also provides a method for preparing a prestressed concrete beam, comprising:
[0106] S1: Mix cement, natural sand, machine-made sand, mine crushed stone and granite to obtain dry material; the mixing time is 120s and the mixing speed is 80r / min.
[0107] S2: Mix nano-silica, clinoptilolite and water, and then perform ultrasonic dispersion to obtain a dispersion; mix and stir the dry material with the dispersion to obtain a wet material; the ultrasonic frequency of the ultrasonic dispersion is 90kHz, and the dispersion time is 60min; the stirring time of the dry material and the dispersion is 80s, and the stirring speed is 60r / min.
[0108] S3: Add aminosulfonate water reducing agent to the wet material and stir to obtain concrete, stirring for 80s at a stirring speed of 125 / min.
[0109] S4: pour concrete into the post-tensioned prestressed concrete beam mold, which is provided with 4 corrugated pipes and is poured in layers; during pouring, vibrating equipment is used for oscillation dispersion, and after pouring, the first curing is performed to obtain a concrete beam blank; the frequency of the oscillation dispersion is 8000vpm, the dispersion time is 15s, and the spacing between the oscillation dispersion points is 50cm; during the first curing, the curing temperature is 45°C, the curing time is 7 days, and the air humidity is 95%. Insert 4 steel strands into the corrugated pipe in the concrete beam blank, and then tension the steel strands, the overall tension control force is P=781.2KN (4×195.3KN), and the steel strands are fixed with a clip-type anchor. After the tensioning is completed, ordinary silicate cement grouting agent is filled into the corrugated pipe and sealed to obtain a prestressed concrete beam blank.
[0110] S5: performing a second curing on the prestressed concrete beam blank and demoulding, curing at 45° C. for 5 days with an air humidity of 95%, and obtaining a prestressed concrete beam after demoulding.
[0111] In step S4, before pouring, a strain gauge is embedded in the concrete beam mold (does not affect the performance, only serves as a test step) for measuring data. After the prestressed concrete beam is obtained, a surface-mounted strain gauge is installed on the prestressed concrete beam (only serves as a test step) for measuring data. In step S5, after the prestressed concrete beam is obtained, it is preserved and cured for 75 days at a temperature of 20°C and an air humidity of 95% (only serves as a test step) to facilitate subsequent data testing; the prestressed concrete beam of this embodiment is subjected to an elastic modulus test and a strain test. The elastic modulus test results are shown in Figure 1 , strain test results are shown in Figure 3 .
[0112] Example 2
[0113] This embodiment provides a prestressed concrete beam and a preparation method thereof. The difference from Embodiment 1 is that the number of clinoptilolite in the raw materials of the concrete is 25 parts, and the water-binder ratio is 0.34.
[0114] The prestressed concrete beam of this embodiment was tested for elastic modulus and strain. The elastic modulus test results are shown in Figure 1 , strain test results are shown in Figure 3 .
[0115] Example 3
[0116] This embodiment provides a prestressed concrete beam and a preparation method thereof. The difference from Embodiment 1 is that the natural zeolite in the raw material of the concrete is chabazite. In step S5: during the second curing, curing is performed at 40° C. for 10 days, and then demolding is performed to obtain a prestressed concrete beam.
[0117] The compressive strength test of the prestressed concrete beam obtained in Example 3 was performed, and the axial compressive strength was 76.2 MPa.
[0118] Example 4
[0119] This embodiment provides a prestressed concrete beam and a preparation method thereof, which differs from Embodiment 3 in that, in step S4: during pouring, ultrasonic oscillation dispersion is performed on the concrete, the ultrasonic frequency is 40 kHz, the dispersion time is 7 s, and the dispersion point spacing of the ultrasonic oscillation dispersion is 80 cm.
[0120] The compressive strength test of the prestressed concrete beam obtained in Example 4 was performed, and the axial compressive strength was 80.5 MPa.
[0121] Example 5
[0122] This embodiment provides a prestressed concrete beam and a preparation method thereof, which is different from Embodiment 1 in that, in step S4: during the first curing, curing is performed at 50° C. for 3 days, and in step S5: during the second curing, curing is performed at 55° C. for 5 days, and then demolding is performed to obtain a prestressed concrete beam.
[0123] Example 6
[0124] This embodiment provides a prestressed concrete beam and a preparation method thereof, which differs from Embodiment 1 in that, in step S4: during the first curing, curing is performed at 40° C. for 7 days, and in step S5: during the second curing, curing is performed at 40° C. for 7 days, and then demolding is performed to obtain a prestressed concrete beam.
[0125] Comparative Example 1
[0126] This embodiment provides a prestressed concrete beam and a preparation method thereof, which is different from Embodiment 1 in that in step S4 and step S5, the curing temperature is 20°C.
[0127] The elastic modulus test was conducted on the prestressed concrete beams of this comparative example. The elastic modulus test results are shown in Figure 1 .
[0128] Comparative Example 2
[0129] This embodiment provides a prestressed concrete beam and a preparation method thereof, which is different from Embodiment 2 in that the number of clinoptilolite in the raw materials of the concrete is 31 parts.
[0130] The elastic modulus test was conducted on the prestressed concrete beams of this comparative example. The elastic modulus test results are shown in Figure 1 .
[0131] Comparative Example 3
[0132] This embodiment provides a prestressed concrete beam and a preparation method thereof, which is different from Embodiment 1 in that nano-silicon dioxide is not included in the concrete raw materials.
[0133] The prestressed concrete beams of this comparative example were subjected to elastic modulus tests and strain tests. The elastic modulus test results are shown in Figure 1 , strain test results are shown in Figure 3 .
[0134] Comparative Example 4
[0135] This embodiment provides a prestressed concrete beam and a preparation method thereof, which is different from Embodiment 1 in that clinoptilolite is not included in the concrete raw materials.
[0136] The prestressed concrete beams of this comparative example were subjected to elastic modulus tests and strain tests. The elastic modulus test results are shown in Figure 1 , strain test results are shown in Figure 3 .
[0137] According to GB / T50081-2019, the compressive strength test of the prestressed concrete beams obtained in Examples 1-2, Examples 5-6 and Comparative Examples 1-4 was performed, and the compressive strength test results are shown in Table 2.
[0138] Table 1 Chemical composition of cement, fly ash, clinoptilolite and nano-silicon dioxide in Example 1
[0139]
[0140] Table 2 Axial compressive strength of concrete beams of Examples 1-2, Examples 5-6 and Comparative Examples 1-4 at different total curing times (Mpa)
[0141] 3 days 7 days 28 days 90 days Example 1 57.6 66.5 77.6 78.6 Example 2 58.1 66.9 76.2 77.1 Example 5 60.5 72.8 none none Example 6 53.2 60.6 none none Comparative Example 1 42.8 49.4 69.1 70.8 Comparative Example 2 49.6 56.3 63.2 65.2 Comparative Example 3 50.4 58.2 67.4 68.4 Comparative Example 4 51.6 61.3 65.9 66.4
[0142] Note: The total curing time is the sum of the curing time in step S4 and step S5 of the concrete beam preparation process.
[0143] According to the data of comparative example 1 of the present invention as the reference curing temperature T0 and the reference curing strength f0, after calculation, the concrete beam blank prepared by the preparation method of embodiment 1 of the present invention has α=0.0142, β=0.0052, and the equation f c(T) =f0(1+α·(T-T0))·e ^(-β·(Ttop-T)) In, Tt op =45℃, T0=20℃, T=45℃, f0=42.8 after curing for 3 days, f0=49.4 after curing for 7 days. It can be estimated that: when the curing time is 3 days, the strength of the concrete beam of Example 1 is 57.96, and when the curing time is 7 days, the strength of the concrete beam of Example 1 is 66.86. The actual measured strength of the concrete beam obtained in Example 1 after curing for 3 days is 57.6, and the strength after curing for 7 days is 66.5, which is in line with expectations.
[0144] The preparation methods and concrete formulas of Examples 5-6 are the same as those of Example 1, and their strengths are also as expected.
[0145] According to the data in Table 2, we can find that:
[0146] Compared with the prestressed concrete beam of comparative example 1, the prestressed concrete beam of embodiment 1 has an early compressive strength that increases significantly faster due to the use of a higher curing temperature in the early stage of curing to induce creep of the prestressed concrete beam, and can reach the expected strength earlier and carry out subsequent treatment; the overall curing time to reach the designed compressive strength is shorter, and the preparation speed of the prestressed concrete beam is faster.
[0147] Compared with the prestressed concrete beam of Example 2, the prestressed concrete beam of Comparative Example 2 has a high water content in the inner layer due to the use of excessive natural zeolite, resulting in a decrease in the ultimate strength of the prestressed concrete beam.
[0148] Compared with the prestressed concrete beam of Example 1, the prestressed concrete beam of Comparative Example 3 does not use nano-silica and lacks the synergistic effect of nano-silica and natural zeolite, so the strength of the final prestressed concrete beam is lower.
[0149] Compared with the prestressed concrete beam of Example 1, the prestressed concrete beam of Comparative Example 4 does not use natural zeolite, resulting in a large loss of water in the concrete beam after high-temperature curing and no replenishment, resulting in a smaller later strength growth and a lower upper strength limit.
[0150] according to Figure 1 Elastic modulus test results and Figure 3 The strain test results show that the prestressed concrete beams of Example 1 and Example 2 have a higher elastic modulus and a stronger ability to resist deformation; the strain rate is slower and has a higher ultimate tensile strength.
[0151] In summary, the prestressed concrete beam and the preparation method thereof of the present invention can solve the problems of more deformation and cracking of concrete beams after long-term use, slow early strength growth of concrete beams and excessively high costs.
[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a prestressed concrete beam, characterized in that: The following steps are involved: S1: Mixing cement, fly ash, fine aggregate and coarse aggregate to obtain dry material; S2: mixing nano-silicon dioxide, natural zeolite and water, and performing ultrasonic dispersion to obtain a dispersion; mixing and stirring the dry material and the dispersion to obtain a wet material; S3: adding a water reducing agent to the wet material and stirring to obtain a concrete slurry; S4: pouring concrete slurry into a post-tensioned prestressed concrete beam mold, and then performing a first curing to obtain a concrete beam blank, the curing temperature being 35-55° C.; applying prestress to the concrete beam blank to obtain a prestressed concrete beam blank; S5: performing a second curing on the prestressed concrete beam blank at a curing temperature of 40-65° C., and obtaining a prestressed concrete beam after curing; In parts by weight, the cement is 400-600 parts, the fly ash is 10-50 parts, the fine aggregate is 400-1000 parts, the coarse aggregate is 800-1200 parts, the natural zeolite is 5-25 parts, the nano-silicon dioxide is 1-10 parts, the water is 100-200 parts, and the water reducing agent is 1-10 parts; the glue-water ratio of the concrete slurry is 1:0.28-0.
4.
2. The preparation method according to claim 1, characterized in that In step S1, the fine aggregate is at least one of natural sand and machine-made sand; the coarse aggregate is at least one of coarse aggregates made of mine crushed stone, slag, granite, basalt and construction waste; the mass of the fine aggregate with a particle size in the range of 0.315 mm to 2.36 mm in the fine aggregate should account for 30-50% of the total mass of the fine aggregate, and the mass of the coarse aggregate with a particle size in the range of 4.75 mm to 19.5 mm in the coarse aggregate should account for 30-50% of the total mass of the coarse aggregate.
3. The preparation method according to claim 1, characterized in that: In step S1, the cement is silicate cement, and the particle size of the cement is 10-25 μm; the particle size of the fly ash does not exceed 20 μm, and the SiO2 content in the fly ash is 15-55wt%, and the Al2O3 content is 5-30wt%.
4. The preparation method according to claim 1, characterized in that: In step S2, the particle size of the nano-silicon dioxide is 1-100 nm, and the purity is ≥95%; the mass of the nano-silicon dioxide with a particle size not exceeding 40 nm should account for 30-50% of the total mass of the coarse aggregate.
5. The preparation method according to claim 1, characterized in that: In step S2, the natural zeolite is at least one of analcime, lazurite, phillipsite, natrolite, mordenite, heulandite, clinoptilolite, chabazite and faujasite; the particle size of the natural zeolite is 10 μm-1 mm, and the porosity is 20-50%.
6. The preparation method according to claim 1, characterized in that: In step S2, the ultrasonic frequency of the ultrasonic dispersion is 60kHz-90kHz, and the dispersion time is 10-100min.
7. The preparation method according to claim 1, characterized in that: In step S3, the water reducing agent is at least one of naphthalene-based, melamine-based, aminosulfonate-based and aliphatic-based.
8. The preparation method according to claim 1, characterized in that: In step S4, the concrete is poured in layers; during the pouring process, the concrete is vibrated and dispersed; during the first curing, the curing time is 3-7 days, and the air humidity is 90-100%; in step S4, when the curing is A days, the temperature condition of the first curing is determined according to the following formula: f c(T) =f0(1+α·(T-T0))·e ^(-β·(Ttop-T)) T0: reference curing temperature, selected according to the standard curing temperature of ordinary concrete; f0: reference curing strength, i.e., the concrete strength after curing for A days at the reference curing temperature T0, in MPa; T: actual curing temperature; f c(T) : Actual strength, i.e. the concrete strength after curing for A days at the actual curing temperature T, in MPa; T top : Hydration active temperature, the temperature at which concrete hydration reaction is most active, measured by experiment; α: early strength growth coefficient, 0<α≤0.1, unitless, measured by experiment; β: active variation coefficient, 0<β≤0.1, unitless, measured by experiment; T0, T, and T top Only the value is taken, no unit is taken; 3≤A≤7.
9. The preparation method according to claim 1, characterized in that: In step S5, during the second curing, the curing time is 1-10 days and the air humidity is 90-100%.
10. A prestressed concrete beam, characterized in that: The prestressed concrete beam is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Novel tension construction method of prestressed concrete structure
CN102587675A
Method for improving strength of steam curing-assisted gel material / cement system
CN108975788A
Machine-made sandstone aggregate prestressed concrete mix proportion design method based on deformation control
CN111798931A
Concrete prefabricated part capable of tensioning prestress in short time and preparation method thereof
CN112521105A